Ethics and Professional Discipline Education in Specialist Medical Education - Yeti Kurniati; Nelawati Nelawati; Erika Srie Mustika; Rezky Muliamarta; Mikael Irfan Limbong; Muhammad Dwi Yuliandy (Global Education Journal, 2026)
Healthcare services are inherently fraught with potential ethical dilemmas and violations of professional discipline, particularly in medical practice involving resident physicians. Resident physicians, while still in their education, perform medical procedures and have ethical and professional responsibilities to patients, colleagues, and institutions. This study aims to examine the regulation of professional ethics for resident physicians based on the Indonesian Code of Medical Ethics (KODEKI) and Minister of Health Regulation Number 3 of 2025, and to analyze the mechanisms for resolving violations of the code of ethics for resident physicians based on these two instruments. The research method used is normative legal research with a statutory and conceptual approach, through a deductive analysis of primary and secondary legal materials. The results indicate that KODEKI functions as an ethical norm that emphasizes the moral values, professionalism, and integrity of physicians, with an enforcement mechanism through the Medical Ethics Honorary Council (MKEK). Meanwhile, Minister of Health Regulation Number 3 of 2025 is an administrative norm that regulates the enforcement of professional discipline through the Professional Discipline Council (MDP) with structured administrative sanctions. Therefore, a comprehensive understanding and consistent implementation are necessary to ensure that the enforcement of professional ethics and discipline for resident physicians is fair, proportional, and in line with the principles of medical education and patient safety.